A critical review of ceramic microbial fuel cell: Economics, long-term operation, scale-up, performances and challenges - Siti Mariam, Daud; Noor Zainura, Zainon; Noor Sabrina, Ahmad Mutamim; Nurul Huda, Baharuddin; Azmi, Aris; Azrul Nurfaiz, Mohd Faizal; Rabialtu Sulihah, Ibrahim; Nuor Sariyan, Suhaimin (Elsevier Ltd, 2024)
Microbial fuel cell (MFC) is a sustainable and renewable technology for applications in power engineering and wastewater treatment. In double chamber MFC, the anode and cathode are separated by a selective membrane, which reduces oxygen transfer, substrate losses and keeps the anode chamber anaerobic. The high price of commercially available membranes, proton exchange membrane (PEM) has accelerated research into substitute materials for use as separators in MFC. Various research identifies low-cost clay-based ceramic materials as one of the most promising substitutes for commercial membranes. These low-cost materials are a viable option for spiked systems due to their low cost, functional long-term robustness, and natural availability. These eco-friendly materials' ability to easily change their microstructure by mixing various compounds into the ceramic raw clay is another benefit of employing them as membranes. The MFC ceramic also ensures stable power output for up to nineteen months in terms of long-term performance reported by previous studies demonstrated a performance of up to 1.56 mW (22.3 W m−3) over a one-year period. The 3-module cascade achieved up to 75 mW (13.9 W m−3) of power, indicating 20 % power loss on day 446, the stack module with 22 MFCs obtained up to 21.4 mW (11.9 W m−3). In the pilot-scale and industrial applications of MFC, the emphasis should not only be on the greatest energy harvesting or recovery but also on the large-scale MFC prototype's economic viability. This review discusses the use of ceramics in MFC for low-cost ceramics, with long-term performance, upscaled, stacked, pilot plant and the challenges of their use in MFC.